A Formal Comparison of Advanced Digital Signature Primitives - Schürmann, Patrick

A Generic Construction of an Anonymous Reputation System and Instantiations from Lattices - Blömer, Johannes; Bobolz, Jan; Porzenheim, Laurens Alexander

A group signature scheme based on the LSRW assumption - Heihoff, Frederic

A Group Signature Scheme from Flexible Public Key Signatures and Structure-Preserving Signatures on Equivalence Classes - Schürmann, Patrick

A Group Signature Scheme with Distributed Group Management - An Application of Threshold Encryption - Löken, Nils

A Practical Second-Order Fault Attack against a Real-World Pairing Implementation - Blömer, Johannes; Gomes da Silva, Ricardo; Günther, Peter; Krämer, Juliane; Seifert, Jean-Pierre (Proceedings of Fault Tolerance and Diagnosis in Cryptography(FDTC))
Several fault attacks against pairing-based cryptography have been described theoretically in recent years. Interestingly, none of these have been practically evaluated. We accomplished this task and prove that fault attacks against pairing-based cryptography are indeed possible and are even practical — thus posing a serious threat. Moreover, we successfully conducted a second-order fault attack against an open source implementation of the eta pairing on an AVR XMEGA A1. We injected the first fault into the computation of the Miller Algorithm and applied the second fault to skip the final exponentiation completely. We introduce a low-cost setup that allowed us to generate multiple independent faults in one computation. The setup implements these faults by clock glitches which induce instruction skips. With this setup we conducted the first practical fault attack against a complete pairing computation.

Analyse und Evaluation eines identitätsbasierten Signcryption-Verfahrens - Liske, Gennadij

Anonymous and Publicly Linkable Reputation Systems - Blömer, Johannes; Juhnke, Jakob; Kolb, Christina (Proceedings of the 18th International Conference on Financial Cryptography and Data Security (FC))
Reputation systems are used to compute and publish reputation scores for services or products. We consider reputation systems where users are allowed to rate products that they purchased previously. To obtain trustworthy reputations, they are allowed to rate these products only once. As long as users rate products once, they stay anonymous. Everybody is able to detect users deviating from the rate-products-only-once policy and the anonymity of such dishonest users can be revoked by a system manager. In this paper we present formal models for such reputation systems and their security. Based on group signatures presented by Boneh, Boyen, and Shacham we design an efficient reputation system that meets all our requirements.

Anonymous credential system based on q-Strong Diffie-Hellman Assumption - Eidens, Fabian

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén